PROYECTO DE INVERSIÓN PARA LA PRODUCCIÓN DE LICOR DE AGAVE EN EL CANTÓN OÑA Y SU COMERCIALIZACIÓN EN LA CIUDAD DE CUENCA - Amay Vargas, Jenifer Mishel (2024)
The investment project aims to determine the feasibility for the production of agave liquor and its commercialization in the city of Cuenca, based on market, technical, economic and financial studies. It is descriptive research, with a mixed approach, techniques such as observation, interview and survey were used, the total population in the city of Cuenca of the urban parishes for the year 2023 is 88.297 inhabitants, 8 suppliers were considered in total between the city of Cuenca, the canton Oña and Nabón. The product to be offered is agave liquor in a 750 ml presentation, which was the most demanded. When analyzing the results, an effective demand in units of 750 ml liquor bottles of 586.714 was determined, the supply in units of 750 ml bottles is 128.189 and the unsatisfied demand is 458.525 bottles of 750 ml, the capacity used will be 12.480 bottles of 750 ml. In the economic and financial study it was determined that an investment of $84.536,53 is required and in the first year the production cost is $146.224,45, generating a profit of $33.355,27. The financial indicators show that the NPV exceeds the initial investment with a total of $40.684,80; the IRR will be 37,69%; the CBR is 0.36 cents obtained for each dollar invested; the capital recovery period will be 2 years, 2 months and 19 days; the project is not sensitive if there is an increase in costs of 14,50% and a decrease in income of 10,61%. It is concluded that with the indicators described above the investment project is feasible and can be implemented.